The Biblical Key Word ḇêraḵ: What Does it Mean and How it Can Be Rendered in English, Arabic and Japanese? - Habib, Sandy (Biblical theology bulletin, 2025)
The Biblical Hebrew word ḇêraḵ (written in Hebrew script ברך and pronounced /beˈraχ/) is a biblical key word that is often rendered in English as bless but also as praise and other words. Since it is a key word, understanding its meaning is important, as this can help Bible readers better understand verses that include it. This can also help practicing Christians and Jews who do not know Hebrew understand prayers based on these verses. Therefore, this paper aims to look into the meaning of ḇêraḵ and explicate it in context using simple, (semi-)universal concepts. The simplicity of the explication makes it easily understood and helps ward off ambiguity. Its (semi-)universality makes it readily translatable into nearly any language. This, in turn, can make the meaning of ḇêraḵ accessible to almost everyone. In addition, we throw light on how this word is and should be rendered in English (the language in which this article is written), Arabic (the mother tongue of the first author), and Japanese (the mother tongue of the second author). Examining the counterparts of ḇêraḵ in these three languages can help English, Arabic, and Japanese translators when translating biblical verses containing this word.